Estimasi Risiko Okratoksin A dari Konsumsi Kopi Bubuk di Indonesia - Arimah Arimah; Ratih Dewanti-Hariyadi; Lilis Nuraida (Jurnal Teknologi dan Industri Pangan, 2022)
Ochratoxin A (OTA) is a nephrotoxic and carcinogenic mycotoxin that can be found in coffee. This study aimed to obtain the processing steps commonly applied by coffee shops in Indonesia, calculate the level of OTA in coffee bean and ground coffee, and the risk estimate of OTA exposure from ground coffee in Indonesia. The processing steps were determined through an online survey while the level of OTA in coffee was calculated from available references. The consumption level of ground coffee was determined from the Indonesia total diet study report and the exposure assessment was carried out by deterministic approach. The risk estimates were expressed as % risk towards provisional tolerable weekly intake (PTWI) and margin of exposure (MOE). Based on the survey of coffee shops (n=20), ground coffee is commonly processed using dry method consisting of cherries sorting, sun drying, roasting and grinding. Ground coffee was the most common coffee consumed by adults. Based on references from countries with climate similar to Indonesia, the level of OTA in coffee bean ranged from 0.033 to 168 μg/kg with an average of 12.25 μg/kg and 0.018-55 μg/kg in ground coffee averaging at 5.60 μg/kg. The individual exposure to OTA from drinking coffee is 0.014-0.744 ng/kg bw/day. The risk estimates shows that risk of ochratoxin A from ground coffee consumption is low, with risk percentage of <100 % provisional tolerable weekly intake (PTWI) and a MOE of higher than 10000 for all age groups. The study suggested that adults (19-55 years) have higher exposure and risk than the other age groups.